Creative activity at higher education institutions: Ukrainian pedagogical overview - Boichenko, M.; Kozlova, T.; Kulichenko, A. K.; Shramko, R.; Polyezhayev, Y.; Куліченко, Алла Костянтинівна (My University, 2022)
Professional training in Ukrainian higher education institutions is primarily focused on strengthening the creative potential of future educators, as it promotes their professional and personal growth, as well as the comprehensive outcome of students’ creative abilities. Therefore, the purpose of this article is to outline the Ukrainian pedagogical experience in enlarging the creative process in higher education institutions. Another aim is to ascertain the concepts of “creative process”, “creativity”, “creative skills” in the up-to-date Ukrainian pedagogical discourse. It is a point of discussion that in Ukrainian pedagogical literature the term “kreatyvnist” (“creativity”) dominates over “tvorchist” (“creative process”). Creative abilities are interpreted as a combination of inner human traits that emerge in the process of activity resulting in innovation. Фахова підготовка в закладі вищої освіти України сфокусована передусім на впотужненні креативного потенціалу майбутніх педагогів, оскільки стимулює їхнє професійне та особисте зростання; ідеться також про реалізацію творчих здібностей здобувача освіти відповідно до вимог сьогодення. Саме тому мету запропонованої наукової розвідки вбачаємо в окресленні українського педагогічного досвіду щодо поглиблення процесу креативності в закладах вищої освіти. Не менш вагома мета полягає в чіткому ранжуванні концептів “креативний процес”, “креативність”, “креативні навички” в педагогічному дискурсі України на етапі сучасся. Дискутивним усе ж лишається питання превалювання терміну “креативність” над “творчість” в українській педагогічній літературі. Креативні здібності так само витлумачують як поєднання внутрішніх, особистих, рис людини, які постають під час діяльності, що має наслідком інновацію.
Креативна діяльність у закладах вищої освіти: український педагогічний вимір
Kulichenko A. K.- https://orcid.org/0000-0003-1469-3816
Keywords: creativity; pedagogical experience; personal evolution; soft skills; Ukrainian higher education institution; креативність; педагогічний досвід; особистісний зріст; м’які навички; заклад вищої освіти України